Our Experience with Iatrogenic Ureteric Injuries among Women Presenting to University College Hospital, Ibadan: A Call to Action on Trigger Factors - Olatunji Lawal; Oluwasomidoyin Bello; Imran Morhason-Bello; Rukiyat Abdus-salam; Oladosu Ojengbede (Obstetrics and Gynecology International)
Background. Ureteric injuries leading to ureterovaginal fistula (UVF) is less common than vesicovaginal fistula, as a cause of urinary incontinence. Recently, there is a surge in the number of UVF cases presenting to University College Hospital (UCH) following a caesarean delivery. The urogynaecology unit at UCH is at the forefront of providing surgical repair for women with all forms of genitourinary fistulas. We describe our experience with managing UVF arising from ureteric injury. Methods. A retrospective data collection of UVF cases managed from January 2012–December 2017 at UCH is presented. Information on sociodemographic and obstetric characteristics, presenting complaints, antecedent surgery, treatment received, findings at surgery, and postoperative complications were obtained with a structured proforma. Results. Eighteen cases of UVFs due to iatrogenic ureteric injury were managed. Majority (N=11; 61.1%) of the women suffered the injury following the emergency caesarean section (EMCS). Abdominal hysterectomy operation accounted for four (22.2%) cases, and one case each (5.6%) was due to vaginal hysterectomy and destructive operations. Prolonged obstructed labour (POL) (81.8%) was the most common indication for the EMCS, while 18.2% had surgery on account of lower uterine segment fibroid. Most of the ureteric injuries were on the left side. Postoperative complications documented were haemorrhage, urinary tract infection, wound infection, and injury to the neighbouring structure. Conclusion. Caesarean section being one of the most performed surgical operations in Nigeria was surprisingly found to be the most common cause of ureteric injury ahead of hysterectomy. It is a pointer that the surgeons might not have properly learnt the art of the caesarean delivery well. We recommend adequate surgical training of medical officers/surgeons that are involved.